EFEKTIVITAS MEDIA KOMIK DALAM MENINGKATKAN KEMAMPUAN MENULIS NARASI PESERTA DIDIK KELAS VII MTS. MAS’UDIYAH WONOMULYO - Daeni Daeni (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2015)
This study aims to determine the extent to which the effectiveness of the comics medium in improving the writing skills of students of class VII MTs.As'adiyah Wonomulyo narrative. The study population were students of class VII MTs. Mas'udiyah Wonomulyo 2013/2014 school year as many as 30 students. Sampling was done by taking a random population (random sampling), observation, testing and interview as a research instrument. Data were analyzed using inferential statistical techniques. Results of research on class VII MTs Mas'udiyah Wonomulyo can be seen in the results of the average value of the pre-test and post-test learners and test value T. From the descriptive statistical analysis performed by the researchers then obtained an average value pre- test and post-test learners. Calculation of t test with SPSS using independent sample test at the 0.05 significance of the results obtained by Sig0,000. That Sig 0.000